2006
DOI: 10.1682/jrrd.2004.10.0135
|View full text |Cite
|
Sign up to set email alerts
|

Use of medical informatics for management of multiple sclerosis using a chronic-care model

Abstract: Abstract-The mission of the Multiple Sclerosis Centers of Excellence (MSCoEs) is to optimize the services veterans with multiple sclerosis (MS) receive across the U.S. Veterans Health Administration. To accomplish this mission, the MSCoE West has adopted a collaborative chronic-disease management strategy along the lines of the model described by Wagner and colleagues. This model describes an organized, integrated, proactive, and population-based approach to patient care that includes healthcare delivery syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A few websites, as the one from the “MS Centers of Excellence” [11], go beyond information and support self-monitoring of the disease. Since MS patients experience a vast array of symptoms that may exacerbate or decrease over time and may suffer also from memory impairment, detailed registration of the symptoms can improve disease management, by allowing more accurate reports to the physician.…”
Section: Introductionmentioning
confidence: 99%
“…A few websites, as the one from the “MS Centers of Excellence” [11], go beyond information and support self-monitoring of the disease. Since MS patients experience a vast array of symptoms that may exacerbate or decrease over time and may suffer also from memory impairment, detailed registration of the symptoms can improve disease management, by allowing more accurate reports to the physician.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedical approaches that use a chronic care model can be implemented on multiple levels for improving the quality of care of patients with MS [12]. In a recent article, Hatzakis et al emphasized the importance of telehealth programs [12], which were defined as "the provision of healthcare and sharing of medical knowledge through telecommunications," for veterans. Hatzakis et al indicated that veterans are often isolated because of their disability or location and telemedicine can significantly improve access to medical care for them.…”
Section: Introductionmentioning
confidence: 99%
“…To translate data into practice, clinicians typically have to: 1) formulate questions that are answerable from the information sources, 2) search for and identify evidence to answer the clinical questions and 3) appraise the evidence identified for quality, reliability, accuracy and relevance [36]. A clinician or a practice team would be greatly supported by an automated clinical reasoning support tool in which available evidence from the literature is selected, deliberated on, summarized, and attuned with guidelines and treatment protocols [16]. A patient's profile, derived from both medical and social data, could form a basis for personalization through which the available evidence could be tailored into relevant instructions for each person involved in the care process.…”
Section: Decision Supportmentioning
confidence: 99%